Power dissipation analysis of PV module under partial shading - Byunggyu Yu; Seok-Cheol Ko (International Journal of Electrical and Computer Engineering (IJECE), 2021)
Photovoltaic (PV) generation has been growing dramatically over the last years and it ranges from small, rooftop-mounted or building integrated systems, to large utility scale power stations. Especially for rooftop-mounted PV system, PV modules are serially connected to match with PV inverter input voltage specification. For serially connected PV system, shading is a problem since the shaded PV module reduces the output whole string of PV modules. The excess power from the unshaded PV module is dissipated in the shaded PV module. In this paper, power dissipation of PV module under partial shading is analyzed with circuit analysis for series connected PV modules. The specific current and voltage operating point of the shaded PV module are analyzed under shading. PSIM simulation tool is used to verify the power dissipation analysis. When there is no bypass diode and three solar modules are connected in series, upto 39.1% of the total maximum PV power is dissipated in the shaded PV module. On the other hand, when the bypass is attached, 0.3% of the total maximum power is generated as a loss in the shaded PV module. The proposed analysis technique of shaded PV module could be used in PV system performance analysis, especially for maximum power point tracking (MPPT) performance.